Structural persistence and surprisal: Implications for proficiency - modulated distributional learning in late bilinguals - Mara Passos Guimaraes (2018)
High-proficiency bilinguals are believed to share abstract structural representations between the first and the second language L1 and L2, respectively (Hartsuiker et al., 2004; Bernolet et al., 2013; Guimarães, 2016; Souza et al., 2014, Souza and Oliveira, 2014). Representational sharing is believed to be modulated by L2 proficiency (Bernolet et al., 2013), construct that relies on levels of language automaticity and loci of memory (implicit or explicit knowledge) to define and measure knowledge of language (Ullman, 2004; Hustijn, 2015). The purpose of this study is to investigate whether high L2 proficiency entails that underlying mechanisms of prediction error and rule abstraction based on distributional learning extends over to L1 processing by late bilinguals. Distributional learning refers to the process of deriving abstract generalizations about language from statistical cues particularly, the frequency distributions of a given aspect of language. The studies in this dissertation were designed to answer questions about L1 Brazilian Portuguese L2 English bilinguals under two competing theories of language learning: a lexical activation account (based on the trailing-activation model proposed by Malhotra et al., 2008) and an implicit learning account (based on the dual-path model proposed by Chang et al., 2006), which differ in their predictions about properties of syntactic persistence (Bock, 1986). Studies 1 and 2 were corpus analyses of passive surprisal-sensitivity and cumulativity of passives in the corpus of spoken BP C-Oral-Brasil I, that aimed to provide syntactic persistence estimates in BP analogous to those of English provided by Jaeger and Snider (2007). Study 3 observed differences in surprisal-sensitivity and cumulativity effects on bilinguals and monolinguals. Results from studies 1 and 2 indicate that the data set for BP did not present priming effects. Study 3 showed an ascending tendency in priming effects on monolinguals, which led to the conjuncture that there is a mechanism of distributional learning that underlies L1 and L2 alike, modulated by proficiency and structural similarity.